Using Focus Groups in the Consumer Research Phase of a Social Marketing Program to Promote Moderate-Intensity Physical Activity and Walking Trail Use in Sumter County, South Carolina - Ericka L. Burroughs, MA, MPH; Lara E. Peck, MPH, CHES; Patricia A. Sharpe, PhD, MPH; Michelle L. Granner, PhD; Carol A. Bryant, PhD; Regina Fields, MS, CHES (Centers for Disease Control and Prevention, 2005)
IntroductionThe use of social marketing approaches in public health practice is increasing. Using marketing concepts such as the "four Ps" (product, price, place, and promotion), social marketing borrows from the principles of commercial marketing but promotes beneficial health behaviors. Consumer research is used to segment the population and develop a strategy based on those marketing concepts. In a community-based participatory research study, 17 focus groups were used in consumer research to develop a social marketing program to promote walking and other moderate-intensity physical activities. MethodsTwo phases of focus groups were conducted. Phase 1 groups, which included both men and women, were asked to respond to questions that would guide the development of a social marketing program based on social marketing concepts. Phase 1 also determined the intervention's target audience, which was irregularly active women aged 35 to 54. Phase 2 groups, composed of members of the target audience, were asked to further define the product and discuss specific promotion strategies. ResultsPhase 1 participants determined that the program product, or target behavior, should be walking. In addition, they identified price, place, and promotion strategies. Phase 2 participants determined that moderate-intensity physical activity is best promoted using the term exercise and offered suggestions for marketing walking, or exercise, to the target audience.ConclusionThere have been few published studies of social marketing campaigns to promote physical activity. In this study, focus groups were key to understanding the target audience in a way that would not have been accomplished with quantitative data alone. The group discussions generated important insights into values and motivations that affect consumers' decisions to adopt a product or behavior. The focus group results guided the development of a social marketing program to promote physical activity in the target audience in Sumter County, South Carolina.